3-stage Hierarchical Quality of Service for Multi-tenant Passive Optical Network - Ruffini, Marco (My University, 2019)
Passive Optical Networks (PONs) are an economically efficient means of providing high bandwidth services to end users. This is because PONs are multi-point shared access medium, where end-points can share the cost and the benefit of fibre optic connection. There is a growing interest in the use of PONs as a bearer for services such as as Long Term Evolution(LTE), at least for the benefit of cost efficiency. However work remains to be done to provide the factors necessary for a service such as LTE, in particular those of stable, low latency and low packet loss transmission, regardless of what other services share the same PON. While services such as LTE required duplex communication channel, in this paper we are mostly concerned with the characteristics of the downstream transmission, so as to further the case for PON sharing. The apportionment of resources is standardised in the upstream,which in effect is a Time Division Multiplexing (TDM) channel,making the Quality of Service (QoS) predictive. In contrast,the downstream is a packetised statistical multiplexed channel similar to a Local Area Network (LAN), requiring additional scheduling architectural components. In this paper, we review typical downstream schedulers used in the industry and propose a three-stage downstream scheduler that assures quality of service, accurately, across Virtual Network Operators (VNOs)in multi-tenant PONs environment. We benchmark our scheduler against other algorithms, obtaining almost ideal scheduling performance.
Optical Networks Design and Modeling (ONDM)
PUBLISHED
Keywords: Slicing; Virtualisation; Passive Optical Networks (PON); Policer; Scheduler; Two Rate Three Color Marker; Quality of Service